Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Choisir le sexe de son enfant ? Nouvelles techniques de procréation assistée en Palestine - Memmi, Sarah; Loû, Annabel Desgrées du (Cahiers du Genre, 2014)
Dans la société palestinienne, avoir un garçon dans sa descendance est un enjeu social majeur, qui dans un contexte de réduction de la fécondité, peut conduire à vouloir choisir le sexe de son enfant. Aujourd’hui, des techniques de sélection sexuelle prénatales performantes sont disponibles et ne font l’objet d’aucune couverture légale. Cet article propose d’analyser les attitudes des Palestiniennes vis-à-vis de la sélection sexuelle, lieu d’une régulation informelle au croisement du religieux, de la pression sociale et des positions personnelles des médecins. Elle crée aussi de nouveaux enjeux dans l’espace israélo-palestinien ; la réglementation et l’accès à ces pratiques sont très différents entre Israël et la Palestine.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; corps; corps des femmes; cours; discipline; justice reproductive; maternité; palestine; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif